Respostas

2014-02-12T19:04:23-02:00
X² - 2x - 15 = 0 ~> a = 1 , b = -2 , c = -15

Δ = b² - 4ac
Δ = (-2)² - 4.1.(-15)
Δ = 4 - (-60)
Δ = 64

x = -b ± √Δ
         2a

x = -(-2) ± √64
           2.1

x = ± 8
        2

x' = 2 + 8  = 10 = 5              x" = 2 - 8 = -6 = -3
         2         2                              2       2

S = {-3 ; 5 } 
1 5 1
2014-02-12T19:05:52-02:00
Δ = b^2 - 4ac
Δ = (-2)^2 - 4(1)(-15)
Δ = 4 +60
Δ = 64

x = -b ± √Δ/2a
x = -(-2) 
± √64 / 2(1)
x = 4 ± 8 / 2

x' = 4 + 8 / 2 = 6
x'' = 4 - 8 / 2 = - 2 

Espero ter ajudado :D